2021
DOI: 10.3390/fermentation7010023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fermented Kefir as Functional Feed Additive in Post-Weaned Pigs

Abstract: The control of the immune system of pigs after weaning is important in pig farming because productivity depends on the survival of the post-weaned pigs. Previously, antibiotics would have been administered in the case of infectious diseases to increase the survival rate of post-weaned pigs, but now, the use of antibiotics is strictly restricted in order to prevent other problems such as the occurrence of antibiotic-resistant pathogens. In this study, the effect of fermented kefir as a functional feed additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Another result showed that the content of free gossypol and glucosinolates in the miscellaneous meal treated with Saccharomyces cerevisiae, Lactobacillus and cellulase decreased significantly, while the content of crude protein, small peptide and amino acid increased [7]. Although the positive role of fermented feed in livestock breeding has been recognized by many researchers, the application effect of A c c e p t e d A r t i c l e fermented feed prepared under different production processes is not very consistent [8][9][10]. In addition, the mechanism of the effect of fermented feed on intestinal microecology needs to be further explored [11].…”
Section: Introductionmentioning
confidence: 99%
“…Another result showed that the content of free gossypol and glucosinolates in the miscellaneous meal treated with Saccharomyces cerevisiae, Lactobacillus and cellulase decreased significantly, while the content of crude protein, small peptide and amino acid increased [7]. Although the positive role of fermented feed in livestock breeding has been recognized by many researchers, the application effect of A c c e p t e d A r t i c l e fermented feed prepared under different production processes is not very consistent [8][9][10]. In addition, the mechanism of the effect of fermented feed on intestinal microecology needs to be further explored [11].…”
Section: Introductionmentioning
confidence: 99%